2016
DOI: 10.1371/journal.pone.0151531
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Volume Changes Caused by the Endoscopic Endonasal Transsphenoidal Approach and Their Effects on Nasal Functions

Abstract: ObjectiveWe evaluated postoperative changes in nasal cavity volume and their effects on nasal function and symptoms after endoscopic endonasal transsphenoidal approach for antero-central skull base surgery.Study DesignRetrospective chart review at a tertiary referral center.MethodsWe studied 92 patients who underwent binostril, four-hand, endoscopic endonasal transsphenoidal approach surgery using the bilateral modified nasoseptal rescue flap technique. Pre- and postoperative paranasal computed tomography and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Of the studies reporting CCSIT outcomes, two studies did not report adequate summary statics for meta‐analysis. These two excluded studies were both from Kim et al, and showed that ESBS was associated with significant changes in nasal cavity dimensions, but these anatomic changes did not correlate with changes in olfaction . In addition, multiple studies showed overlapping cohorts from the same study group, and thus three additional studies were excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the studies reporting CCSIT outcomes, two studies did not report adequate summary statics for meta‐analysis. These two excluded studies were both from Kim et al, and showed that ESBS was associated with significant changes in nasal cavity dimensions, but these anatomic changes did not correlate with changes in olfaction . In addition, multiple studies showed overlapping cohorts from the same study group, and thus three additional studies were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…These two excluded studies were both from Kim et al, and showed that ESBS was associated with significant changes in nasal cavity dimensions, but these anatomic changes did not correlate with changes in olfaction. 44,45 In addition, multiple studies showed overlapping cohorts from the same study group, and thus three additional studies were excluded. Only the studies with the most comprehensive cohort were included in the meta-analysis.…”
Section: Quantitative Analysis/meta-analysismentioning
confidence: 99%
“…In addition, there are some limitations involving this technique related to surgical instrumentations and limited work space [35, 36, 37]. The workspace boundary could be described along with the surgical approach in addition to the volume constraint [37,40,41]. Satisfactory information about the workspace characteristics makes it a practical new modality for robotic workspace classification.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the sample‐size calculation, Kim et al 17,18 have reported that ILST‐induced intranasal volume changes do not correlate with objective olfactory changes after binostril EETS, suggesting that the overall impact of ILST on olfaction is minimal. In an earlier study of endoscopic sinus surgery (ESS), the incidence of objective olfactory decline after PRST was 12% in patients with chronic rhinosinusitis 19 .…”
Section: Methodsmentioning
confidence: 99%